Chiral Capillary Electrophoresis with On-Line Sample Preparation - Mikus, Peter; Marakova, Katarina (Current Pharmaceutical Analysis, 2010)
An advanced capillary electrophoresis (CE) based on the on-line combination of the CE with a sample preparation procedure (preconcentration, purification, analyte derivatization) is presented and supplemented by applications in the field of an ultratrace chiral determination of biologically active compounds. A brief description of theory, benefits and limitations is given for many applicable (i) electrophoretic techniques (stacking) and (ii) nonelectrophoretic techniques (chromatography, extraction, membrane filtration/dialysis, flow injection) implemented in conventional CE for the effective on-line sample preparation. Practical potentialities of such CE hyphenations are demonstrated on many application examples aimed mainly to biological matrices and monitored within the period of last decade in the present review paper. Perspectives for full automatization and miniaturization linked with this analytical strategy can offer new insight into biomedical analytical research/practice in near future. It should also be realized that while this review is limited to chiral separation, the techniques are generally applicable.
Keywords: Derivatization